2015
DOI: 10.3846/20294913.2015.1072752
|View full text |Cite
|
Sign up to set email alerts
|

The International Strengthening of Ipr and Air Pollution Abatement: The Role of the Trips Agreement

Abstract: Abstract. This paper comes in the wake of the literature considering technological progress as the main device to offset air pollution caused by economic activity. The issue has been extensively studied in general, but there is no previous research on the effects that an international strengthening of legal protection of Intellectual Property Rights (IPR) due to the Uruguay Round Agreement and the Annex on Trade-Related aspects of the IPR (TRIPs, for short), underwritten in 1994, may have had on worldwide emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
(81 reference statements)
0
0
0
Order By: Relevance
“…Research on the environmental aspect is limited, with only a few scholars exploring the influence of IP protection on environmental pollutants. Di Vita et al 41 contend that the IP protection system, as a crucial institutional safeguard for environmental quality, aids in mitigating haze pollution and enhancing environmental conditions.…”
Section: Related Workmentioning
confidence: 99%
“…Research on the environmental aspect is limited, with only a few scholars exploring the influence of IP protection on environmental pollutants. Di Vita et al 41 contend that the IP protection system, as a crucial institutional safeguard for environmental quality, aids in mitigating haze pollution and enhancing environmental conditions.…”
Section: Related Workmentioning
confidence: 99%
“…Only a few scholars have explored the environmental effects of IPP. Di Vita (2017) [21] found that enhancing the level of uniform minimum standards of IPP among World Trade Organization member countries may help reduce air pollution emissions. Hao et al (2021) [22] included IPP, trade, foreign direct investment, and outward foreign direct investment in China in a unified analytical framework, using a dynamic threshold regression approach, and showed that trade technology spillovers can reduce carbon emissions only if the regional IPP level exceeds the threshold.…”
Section: Introductionmentioning
confidence: 99%